Calretinin immunohistochemistry in Hirschsprung’s disease: An adjunct to formalin-based diagnosis - Ayper KAÇAR; Ata Türker Arıkök; Müjdem Nur AZILI; Tuğrul TİRYAKİ (Turkish Journal of Gastroenterology, 2019)
-